The effect of financial performance, board of commissioners, blockholder ownership, auditor type and firm age on voluntary disclosure - Aldo Prandita Nanda; Joicenda Nahumury (STIE Perbanas Surabaya, 2018)
Disclosure of information reflects the presentation of the company's annual report. One general purpose of disclosure is as a basis for decision making. This study aims to examine the effect of financial performance (ROA, DER, CR), board of commissioners (BS, BI), blockholder ownership, auditor type, and firm age on voluntary disclosure. The population of this study is mining companies listed on the Indonesian Stock Exchange period 2012-2016. The number of data is 196. Sampling is conducted using purposive sampling method. The data analysis technique used in this study is SEM-PLS with SmartPLS 3.0 program. The results of data analysis show that firm age has no effect on voluntary disclosure, while blockholder ownership has a significant negative effect on voluntary disclosure. Financial performance, board of commissioners and auditors type have a significant positive effect on voluntary disclosure. The impact of this research is that voluntary disclosure can be used to increase the completeness of company information for investors and creditors.